Stereotype, Prejudice And Social Distance In Multiethnic Society - Masdar, Muhammad; Harifuddin, Harifuddin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
Social harmony is embodied condition of their togetherness, shared values, shared expectations prevailing in social life. In that context, the symbol of interaction used to understand the process of how individuals primarily from various ethnic interpreted and give meaning to the symbols concerning the events and situations in everyday life interaction. In the process of inter-ethnic interaction, individuals influenced by their perceptions of other ethnic groups. The elements in the concept of the interaction of these perceptions are stereotypes, prejudices, and social distance. These three aspects are mental-creative dimensions and the basis of the ongoing process of interaction of quality and sustainable. Stereotyping is often also called